2023
DOI: 10.3390/cancers15205070
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Health Disparity: Pharmacologic Anthropology

Nathan R. Wall,
Ryan N. Fuller,
Ann Morcos
et al.

Abstract: Pancreatic cancer (PCa) remains a formidable global health challenge, with high mortality rates and limited treatment options. While advancements in pharmacology have led to improved outcomes for various cancers, PCa continues to exhibit significant health disparities, disproportionately affecting certain populations. This paper explores the intersection of pharmacology and anthropology in understanding the health disparities associated with PCa. By considering the socio-cultural, economic, and behavioral fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 256 publications
0
3
0
Order By: Relevance
“…Despite advances in diagnostics and therapeutics, PC remains a very challenging condition to treat, with consistently high mortality rates and limited available treatments 40,41 . Recently, research has focused on identifying prognostic markers for PC, and preclinical studies have identified several prognostic lncRNA signatures 8,[42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in diagnostics and therapeutics, PC remains a very challenging condition to treat, with consistently high mortality rates and limited available treatments 40,41 . Recently, research has focused on identifying prognostic markers for PC, and preclinical studies have identified several prognostic lncRNA signatures 8,[42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Socio-cultural dynamics play a significant role in shaping health behaviors. Strategic community engagement involves understanding and navigating these dynamics (Wall, et al,2023). This includes addressing cultural norms, language barriers, and socio-economic factors that may influence vaccine acceptance.…”
Section: Strategic Approaches In Vaccinationmentioning
confidence: 99%
“…CR in PCa research plays a crucial role in addressing health disparities by enabling the study of patient-derived samples. Through CR methodology, researchers can investigate the molecular mechanisms underlying these disparities, identifying genetic, epigenetic, and environmental factors contributing to differential outcomes [ 84 ]. By understanding the root causes of health disparities, CR facilitates the development of targeted interventions and precision medicine approaches tailored to high-risk populations, ultimately aiming to reduce the unequal burden of PCa.…”
Section: Applications Of Cr Cells In Pca Initiation and Progressionmentioning
confidence: 99%